The Rate of Cisplatin Dosing Affects the Resistance and Metastatic Potential of Triple Negative Breast Cancer Cells, Independent of Hypoxia - Omkar Bhatavdekar; Inês Godet; Daniele Gilkes; Stavroula Sofou (MDPI AG, 2022)
To best control tumor growth and/or metastasis in triple negative breast cancer (TNBC), it may be useful to understand the effect(s) of chemotherapy delivery (i.e., the rate and pattern of exposure to the drug) on cell sub-populations that have experienced different levels of hypoxia (and/or acidosis). In this spirit, MDA-MB-231 TNBC cells, and their hypoxia-reporter counterparts, were characterized for their sensitivity to cisplatin. When in the form of multicellular spheroids, that capture the diffusion-limited transport that generates hypoxic and acidic subregions within the avascular areas of solid tumors, the effects of the rate and pattern of exposure to cisplatin on cell viability and motility/migration potential were evaluated for each cell sub-population. We demonstrated that cell sensitivity to cisplatin was not dependent on acidosis, but cell resistance increased with exposure to hypoxia. In spheroids, the increase of the rates of cell exposure to cisplatin, at a constant cumulative dose, increased sensitivity to chemotherapy and lowered the cells' metastatic potential, even for cells that had experienced hypoxia. This effect was also shown to be caused by nanocarriers engineered to quickly release cisplatin which deeply penetrated the spheroid interstitium, resulting in the fast and uniform exposure of the TNBC tumors to the agent. This rate and dosing-controlled model may effectively limit growth and/or metastasis, independent of hypoxia. This mode of chemotherapy delivery can be enabled by engineered nanocarriers.